Studies in exegesis : Christian critiques of Jewish law and rabbinic responses, 70-300 C.E. - Basser, Herbert W. (Brill reference library of ancient Judaism ;, 2000)
The author examines debates between Christians and Jews in the process and aftermath of the Christian break from Judaism. By closely examining the exegetical underpinnings of the controversies between Jews and Christians, the author discovers the Jewish side.